Potential Benefits and Implications of Applying MDR in Food-Based Products - Risikko, Cecilia (My University, 2025)
The definition of a medical device has expanded during the recent years, and today also food-based products can under certain conditions qualify as CE marked medical devices. The purpose of this thesis is to clarify these circumstances and the benefits of a CE marking, and thus, to explore whether a section of food-based products should utilise the route of medical devices more often. To succeed in this, documents, directives, and regulations of European Union and Finnish Authorities are examined, some companies from the industry interviewed, and a questionnaire on pharmacists’ opinions on the topic conducted. The findings of the thesis show that food supplements with health claims and medical devices have overlapping sections. The mechanisms of actions of the two concepts, however, are different according to the strict definitions. As an example of a food-based product, xylitol pastilles may have a chance in qualifying as a medical device due to the properties, which are similar to a CE marked case example examined, Lingora®. The results of the questionnaire show that the CE marking is highly trusted by pharmacists and customers of pharmacies. This topic must be further studied to obtain more clarity and to utilise its full potential.
Keywords: food-based medical device, CE marking, MDR, medical device, health claim, food supplement, food-based product, xylitol